Kajian Yuridis Pasal 362 Kitab Undang-Undang Hukum Pidana dan Pasal 30 Undang-Undang Nomor 11 tahun 2008 tentang Informasi Dan Transaksi Elektronik Terhadap Pencurian Internet Wifi - Junaidi Junaidi (Wajah Hukum, 2020)
The use of private wifi internet, especially at home, has become commonplace, wifi internet is used without permission from the owner, especially without his knowledge, if this happens it will result in the owner experiencing losses. Home wifi internet that should be used by the family but is also enjoyed by other people without the permission and knowledge of the owner, the owner who pays but other people use it. The crime of theft is regulated in Article 362 of the Criminal Code, while Article 3o of Law Number 11 of 2008 concerning Electronic Information and Transactions is more about illegal access. The application of criminal law ini the crime of theft of internet wifi, as regulated in : a) Article362 of the Criminal Code, internet wifi can be interpreted extensively as one form of “goods” which in an element of Article 362 of the Criminal Code, this can be equated with “electricity” and “gas” although it does not have a from, is not visible and felt, but has an economic value to be said as “goods” because to be able to use or enjoy wifi internet service users must purchase a wifi internet package first; b) Article 30 paragraph (1), (2) dan (3) Law Number 11 of 2008 concerning Electronic Information and Transaction may be imposed on perpetrators of wifi internet theft because it is related to illegal access. The act of stealing internet quota by using software or computer applications to break into the internet network to obtain a wifi internet username and password in order to gain access using wifi internet. In the settlement of a criminal act, proof is essential, because in the settlement of a criminal case what is sought is a material truth.